Dead Man's Eyes - Roberts, J. R. (New York A Jove book, 2002)
Clint Adams heads home to Labyrinth, Texas, in hopes of settling down. But he's soon asked for his help by Emma Deerborne, a woman on the run for a Sioux warrior who's convinced she is responsible for a curse put upon his tribe. (June)
Keywords: Western stories